Susceptibility of stock market returns to international economic policy: Evidence from effective transfer entropy of Africa with the implication for open innovation - Anokye M. Adam (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study contributes to the scant finance literature on information flow from international economic policy uncertainty to emerging stock markets in Africa, using daily US economic policy uncertainty as a proxy and the daily stock market index for Botswana, Egypt, Ghana, Kenya, Morocco, Nigeria, Namibia, South Africa, and Zambia from 31 December 2010 to 27 May 2020, using the Rényi effective transfer entropy. International economic policy uncertainty transmits significant information to Egypt, Ghana, Morocco, Namibia, and South Africa, and insignificant information to Botswana, Kenya, Nigeria, and Zambia. The asymmetry in the information transfer tends to make the African market an alternative for the diversification of international portfolios when the uncertainty of the global economic policy is on the rise. The findings also have implications for the adoption of open innovation in African stock markets.
Keywords: 650; African stock markets; economic policy uncertainty; effective transfer entropy; Rényi transfer entropy